2019
DOI: 10.4274/tjod.galenos.2019.19577
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress in cervical cancer and its response to chemoradiation

Abstract: Amaç: Büyük bir sosyal ve ekonomik yükü olan rahim ağzı kanseri, dünya genelindeki kadınlar arasında kansere bağlı ölümlerin önde gelen nedenlerinden biridir. Erken evrelerdeki tanısı, mortalite ve morbidite oranlarını azaltabilmektedir. Bu çalışma, oksidatif stres düzeyini ve kemoradyasyonun etkisini belirlemek için rahim ağzı kanserli hastalarda serum total antioksidan kapasitesi (TAK) ile malondialdehit (MDA) ve bakır konsantrasyonlarının durumunu değerlendirmek amacıyla yapıldı. Gereç ve Yöntemler: Onkoloj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Our results are consistent with the results of other investigations. In another report, the TAC levels in cervical cancer patients and controls were 1320 ± 0.029 SD lmol Trilox equivalent/L and 1620 ± 0.042 SD lmol Trilox equivalent/L, respectively [33]. Subramanyam reported TAC levels in cervical cancer patients and controls as 1000.2 ± 2.44 SD lmol Trilox equivalent/L and 3100 ± 1.24 SD lmol Trilox equivalent/L, respectively, which is similar to our findings [34].…”
Section: Discussionmentioning
confidence: 85%
“…Our results are consistent with the results of other investigations. In another report, the TAC levels in cervical cancer patients and controls were 1320 ± 0.029 SD lmol Trilox equivalent/L and 1620 ± 0.042 SD lmol Trilox equivalent/L, respectively [33]. Subramanyam reported TAC levels in cervical cancer patients and controls as 1000.2 ± 2.44 SD lmol Trilox equivalent/L and 3100 ± 1.24 SD lmol Trilox equivalent/L, respectively, which is similar to our findings [34].…”
Section: Discussionmentioning
confidence: 85%
“…HT pathophysiology in diabetics involves complex interactions with many environmental factors and between the nervous, cardiovascular and renin-angiotensin systems (5). It also includes physiological changes such as increased levels of blood sugar levels and abnormal levels of lipids, increased oxidative stress, chronic inflammation, hypoxia and ischemia (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…CC patients had the highest Cu concentrations [178], and this increase was positively correlated with the stages of the disease, while Cu decreased after different treatments (surgery, chemotherapy, radiotherapy, or a combination of both) [179]. This result differs from a study where the authors observed that increased serum Cu levels were not modified after chemoradiotherapy in patients with CC [180]. In summary, Cu is indicated as a possible risk factor associated with CC that could be useful to monitor this type of cancer and potentially to control the progress of the disease [177][178][179].…”
Section: Uterine Diseases 221 Uterine Cervix Cancermentioning
confidence: 61%